Analisis Pengaruh Marketing Mix 7p (Product, Promotion, Price, Place, People, Process, And Physical Evidence) Terhadap Keputusan Pembelian Konsumen Mie Gacoan Di Kota Pati - febrima, Achmad yoki; mashuri, Dian imami; ikawati, amalia dewi (YUME : Journal of Management, 2025)
Competition between brands and products is very intense, forcing companies to not only survive but also continue to grow. Companies need to focus on important things, such as maintaining existing customers and actively attracting potential customers. The goal is that customers do not switch to competitors and remain loyal to the company. Noodles have become a trendy menu that is modified and varied in terms of products and how they are processed. This type of modern noodle processing is in great demand by business actors, including in Pati City. This study uses the convenience sampling method rather than nonprobability sampling because the population is large and not yet known for certain. The purpose of this study was to determine whether the variables Product (X1), Promotion (X2), Price (X3), Place (X4), People (X5), Process (X6), and Physical Evidence (X7) have an influence on the purchasing decisions of gacoan noodle consumers in Pati City (Y). The results of multiple regression analysis show that there is a correlation of 0.798 between the purchasing decisions of gacoan noodle consumers and product, price, promotion, place, people, process, physical evidence. The correlation value is R2 0.636. The results of the study showed that the variables product, price, promotion, place, people, process, physical evidence gave a positive influence of 63.6% on the purchasing decision of consumers of mie gacoan; other factors that have not been studied gave an influence of 36.4%. Keywords: product, price, promotion, place, people, process, physical evidence